Aricidea fragilis (Annelida: Paraonidae) in the Mediterranean Sea: overlooked native or alien species?. Issue 1 (1st January 2018) - Langeneck, J.; Mazziotti, C.; Mikac, B.; Scirocco, T.; Castelli, A.
Abstract: The paraonid polychaete Aricidea fragilis Webster, 1879, a typically west-Atlantic species, is reported from the Mediterranean Sea on the basis of several individuals, from the Adriatic and Tyrrhenian Sea. Its differences with the other Mediterranean Paraonidae, and in particular with the morphologically close Aricidea suecica meridionalis Laubier & Ramos, 1974, are briefly discussed. The possible status of A. fragilis as an alien species in European waters is analysed. The scarcity of historical records, the relatively restricted distribution, and the population dynamics observed in European waters strongly support the hypothesis of an introduction, despite the wide temporal interval between the first record of the species in the 1930s and the currently ongoing range expansion and population explosion. Here we precautionarily suggest considering A. fragilis a cryptogenic species.